THE EFFECT OF FIRM SIZE, LEVERAGE, PROFITABILITY, AND CAPITAL STRUCTURE ON PROPERTIES AND REAL ESTATE FIRM VALUE (Jurnal Ipteks Terapan, 2024)
This researh aims to determine the effect of the firm size, leverage, profitability, and capital structure of the firm value of service companies in the properties and real estate sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019 – 2022. The independent variables used in this research are the firm size, leverage, profitability, and capital structure. The dependent variable used in this research is firm value with indicators of Tobin’s Q ratio. This research uses secondary data with a total sample of 17 companies. The result of this research showed that profitability partially effect the firm value insignificantly. Firm size, leverage, and capital structure does not have a significant partial effect on firm value. While simultaneously showed that firm size, leverage, profitability, and capital structure does not effect the firm value.Keywords: Firm Size, Leverage, Profitability, Capital Structure, Firm Value